Solitary Hepatic Nodule Adjacent to the Right Portal Vein: A Common Finding of Alagille Syndrome?. Issue 2 (February 2016) - Alhammad, Abdullah; Kamath, Binita M.; Chami, Rose; Ng, Vicky L.; Chavhan, Govind B.
ABSTRACT: Background: Hepatic lesions have been described in Alagille syndrome (ALGS) in isolated case reports, and most of these have been reported to be hepatocellular carcinoma. Objectives: The aim of the present study was to determine the frequency, imaging, and histopathologic characteristics of hepatic lesions in children with ALGS. Methods: Available abdominal imaging of children with ALGS was retrospectively reviewed to note the presence of any focal liver lesion, its location, and imaging characteristics. Other findings including signs of portal hypertension, portal lymph nodes, and splenic and renal abnormalities were also noted. Findings were correlated with pathology in available cases and with clinical follow-up. Results: Of 55 children with clinically and/or genetically confirmed ALGS followed in the liver clinic, 39 (19 boys, 20 girls; mean age 8.9 years) with imaging available on picture archival and communication system were included in the study. Focal hepatic lesions were seen in 12 of the 39 (30%) children, solitary in 11 and multiple in 1. Ten of these children had a large nodule adjacent to the right portal vein. The median diameter of the lesions was 8.1 cm (range 5.6–9.8 cm). Magnetic resonance imaging features and pathology in available cases were suggestive of a regenerative nodule. α-fetoprotein levels were normal in all except 1 child who had mild elevation. Conclusions: Combining our series and previous case reports, the presence of a large nodule adjacent to the right portal vein appears to be a common finding in ALGS. The typical location, normal α-fetoprotein levels, and magnetic resonance imaging features with vessels coursing through the lesion can reliably differentiate this benign nodule from hepatocellular carcinoma.